2017
DOI: 10.3390/rs9090957
|View full text |Cite
|
Sign up to set email alerts
|

Use of Miniature Thermal Cameras for Detection of Physiological Stress in Conifers

Abstract: Tree growth and survival predominantly depends on edaphic and climatic conditions, thus climate change will inevitably influence forest health and growth. It will affect forests directly, for example, through extended periods of drought, and indirectly, such as by affecting the distribution and abundance of forest pathogens and pests. Developing ways of early detection and monitoring of tree stress is crucial for effective protection of forest stands. Thermography is one of the techniques that can be used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Apart from errors associated with the LST retrieval and the UAV-thermal sensor itself, there are also errors related to the underlying structure from motion process used to construct the ortho-rectified UAV-based thermal maps. Studies have already reported that the SfM process struggles to stitch thermal images into an accurate orthomosaic [49,73], since these contain reduced information compared to RGB images, rendering the detection of common feature points more challenging. SfM is based on both the images position and also the capacity to match pixels for georeferencing and correcting image distortion.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from errors associated with the LST retrieval and the UAV-thermal sensor itself, there are also errors related to the underlying structure from motion process used to construct the ortho-rectified UAV-based thermal maps. Studies have already reported that the SfM process struggles to stitch thermal images into an accurate orthomosaic [49,73], since these contain reduced information compared to RGB images, rendering the detection of common feature points more challenging. SfM is based on both the images position and also the capacity to match pixels for georeferencing and correcting image distortion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the thermal image can be unreliable especially when the internal temperature of the camera is changing rapidly, such as during camera warmup period or during the flight when a gust of cool wind results in cooling of the camera. To overcome this challenge, the user may need to provide sufficient startup time before operation (preferably 30-60 min) [102,[143][144][145], shield the camera to minimize the change in the internal temperature of the camera [142], calibrate the camera [146][147][148][149][150][151][152][153], and perform frequent flat-field corrections.…”
Section: Thermalmentioning
confidence: 99%
“…Key considerations relate to spatial resolution and thermal sensitivity, with the latter now achieving 40-50 mK. Thermal UAS remote sensing also requires consideration of radiometric calibration and accounting for vignetting and other systematic effects, as discussed by Smigaj et al [57]. With the aim to provide a description of the potential of a thermal camera mounted on a UAS, an example of a thermal image providing the surface temperature (in degrees Celsius) obtained over a vineyard of Aglianico is given in Figure 2.…”
Section: Sensorsmentioning
confidence: 99%